KARAKTERISTIK KIMIA DAN ORGANOLEPTIK: Sosis Biji Nangka (Artocarpus Heterophyllus) - Meganiva Putri Cahyati, MAP (2020)
Vegetarians had nutritional problems that considered such as deficiency of protein nutrients. Based on chemical composition, especially protein, jackfruit seeds has the potential that processed into food alternative dishes with protein in the form of sausages that has an economical value and favored by various people. The purpose of this research was to determine the characteristic of sausage seeds (Arthocarpus heteropillus). The method in this study used the experimental method of complete random draft design (RAL) with 3 formulations, namely F1 (jackfruit seeds 100 g: cornstarch 75 g), F2 (jackfruit seeds 132.5 g: cornstarch 42.5 g), as well as F3 (jackfruit seeds 165 g: cornflour 10 g). Based on the hedonic quality at all attributes (color, aroma, flavor, and texture) the jackfruits seeds sausage there was a very noticeable difference (P < 0.01) in each treatments (F1, F2, dan F3). Based on the hedonic at attributes of color, flavor, and texture the jackfruits seeds sausage there was a very noticeable difference (P < 0.01) in each treatments (F1, F2, dan F3), and at attributes of scent the jackfruits seeds sausage there was noticable difference (P< 0.05) in each treatments (F1, F2, dan F3). The Bayes method test results show that F1 is the chosen formula based on the ranking results in consideration of organoleptic test, the weight value reaches 2.997. The selected Formula has 51.91% water, 4.03% ash, 6.25% protein, 0.75% fat, and 37.06% carbohydrate.